2021
DOI: 10.1371/journal.pone.0256443
|View full text |Cite
|
Sign up to set email alerts
|

Comparing growth velocity of HIV exposed and non-exposed infants: An observational study of infants enrolled in a randomized control trial in Zambia

Abstract: Background Impaired growth among infants remains one of the leading nutrition problems globally. In this study, we aimed to compare the growth trajectory rate and evaluate growth trajectory characteristics among children, who are HIV exposed uninfected (HEU) and HIV unexposed uninfected (HUU), under two years in Zambia. Method Our study used data from the ROVAS II study (PACTR201804003096919), an open-label randomized control trial of two verses three doses of live, attenuated, oral RotarixTM administered 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 33 publications
2
6
0
Order By: Relevance
“…We found no statistically significant difference in WAZ, HAZ, and WHZ in HEU compared with HUU children. Our findings are consistent with a study from Zambia [22] but differ from other studies in Nigeria [19], Malawi and Uganda [20], and Kenya [18], which found that HEU children had lower WAZ, HAZ, and WHZ. A study in Botswana also observed a higher risk of stunting in HEU than in HUU children [7].…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…We found no statistically significant difference in WAZ, HAZ, and WHZ in HEU compared with HUU children. Our findings are consistent with a study from Zambia [22] but differ from other studies in Nigeria [19], Malawi and Uganda [20], and Kenya [18], which found that HEU children had lower WAZ, HAZ, and WHZ. A study in Botswana also observed a higher risk of stunting in HEU than in HUU children [7].…”
Section: Discussionsupporting
confidence: 85%
“…A study in Botswana also observed a higher risk of stunting in HEU than in HUU children [7]. Most of these studies demonstrating growth deficits in HEU used data collected at or before 2014 (when Option B+ was rolled out) [18–20,22]. Our study and the study in Zambia [22] that found no difference in growth between HEU and HUU children both used data after 2017.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…All covariates in univariable analyses with a p -value of 0.10 were included in multivariable analyses. Additionally, an a priori decision was made to include maternal age in the multivariable model, regardless of univariable p-value [ 3 , 32 , 33 ]. Infant feeding practice was defined as exclusive breastfeeding, formula feeding, or mixed feeding based on maternal report.…”
Section: Methodsmentioning
confidence: 99%